2020
DOI: 10.1177/0898264320975231
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Military Service Exposures and Psychological Resilience on the Mental Health Trajectories of Older Male Veterans

Abstract: Objectives: We examine the impact of exposure to the dead, dying, and wounded (DDW) during military service on the later-life depressive symptom trajectories of male United States veterans, using psychological resilience as an internal resource that potentially moderates negative consequences. Methods: The Health and Retirement Study (2006–2014) and linked Veteran Mail Survey were used to estimate latent growth curve models of depressive symptom trajectories, beginning at respondents’ first report of resilienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Military personnel often face higher mental health risks than do civilians owing to their occupational characteristics of chronic exposure to high-pressure environments (6). In the existing literature, topics related to the mental health of military personnel are often based on clinical outcomes, such as a high incidence of psychiatric problems (e.g., anxiety, depression, and posttraumatic stress disorder) and increased rates of suicide (10)(11)(12). Due to the significant increase in military personnel experiencing mental health problems, it is critical to develop strategies to prevent psychological symptoms from developing into more serious psychiatric problems (13).…”
Section: The Effect Of Resilience On Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Military personnel often face higher mental health risks than do civilians owing to their occupational characteristics of chronic exposure to high-pressure environments (6). In the existing literature, topics related to the mental health of military personnel are often based on clinical outcomes, such as a high incidence of psychiatric problems (e.g., anxiety, depression, and posttraumatic stress disorder) and increased rates of suicide (10)(11)(12). Due to the significant increase in military personnel experiencing mental health problems, it is critical to develop strategies to prevent psychological symptoms from developing into more serious psychiatric problems (13).…”
Section: The Effect Of Resilience On Mental Healthmentioning
confidence: 99%
“…Extensive research has confirmed that resilience reduces the likelihood of mental health issues (12,(14)(15)(16)(17). Psychological resilience is seen as a positive psychological quality that can counteract the adverse effects of stressors, allowing individuals to experience fewer negative emotions, cope better in the face of unexpected events, and have a greater sense of subjective well-being (9,18).…”
Section: The Effect Of Resilience On Mental Healthmentioning
confidence: 99%